Automatic Double Can Crusher Prototype Development - Adib Farhan Badrol Isa; Nurul Hanna Mas’aud; Nur Aini Sabrin Manssor; Nurrul Amilin Zainal Abidin; Norjasween Abdul Malik (Journal of Advanced Mechanical Engineering Applications, 2026)
An awareness about recycling among Malaysian keep on increasing as most Malaysian are well educated since kindergarten level. Many activities have been conducted to encourage young children to recycle. Unfortunately, the process of recycling the tin can be difficult to be done by children. Traditional manual crushers required substantial physical effort or expensive pneumatic systems. Therefore, this study is conducted to design and fabricate a prototype of automatic can crusher where this electrically operated solution prioritizes cost-effectiveness and user safety. The process starts with problem identification, followed by concept generation by using morphological chart, then design selection using Pugh chart. The process continues with 3D design model using SolidWorks, fabrication process and testing. The output product is expected to enhance productivity of can recycling and safety, reduce time and efficient. Experimental results confirm that this product saves significant time and human energy, processing approximately 12 cans per minute. This innovation supports sustainability goals by facilitating easier waste transport and promoting efficient aluminum recycling.